Immaterialism and Realism in Berkeley - Defez, Antoni (Pensamiento. Revista de Investigación e Información Filosófica, 2016)
In this paper Berkeley’s arguments for immaterialism are analyzed. Special attention is devoted to a priori argument underlying the motto esse est percipi and, in particular, the way in which Berkeley understands the concept of existence and the metaphysical value of its meaning. Likewise, it is also explained how this immaterialism is a spiritualism or theological realism serving apologetic ends.